Enhancing epitope of PEDV spike protein - Thavorasak, Techit; Chulanetra, Monrat; Glab-ampai, Kittirat; Mahasongkram, Kodchakorn; Sae-lim, Nawannaporn; Teeranitayatarn, Karsidete; Songserm, Thaweesak; Yodsheewan, Rungrueang; Nilubol, Dachrit; Chaicumpa, Wanpen; Sookrung, Nitat (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) is the causative agent of a highly contagious enteric disease of pigs characterized by diarrhea, vomiting and severe dehydration. PEDV infects pigs of all ages but neonatal pigs during the first week of lives are highly susceptible; the mortality rates among the newborn piglets may reach 80-100%. Thus, PEDV is regarded one of the most devastating pig viruses that cause huge economic damage to pig industries worldwide. Vaccination of sows and gilts at pre-fertilization or pre-farrowing is a good strategy for prevention of suckling piglets against PEDV through acquisition of the lactating immunity. However, vaccination of the mother pigs for inducing high level of virus neutralizing antibodies is complicated with unstandardized immunization protocol and unreliable outcome. Besides, the vaccine may also induce enhancing antibodies that promote virus entry and replication, so called antibody-dependent enhancement (ADE), which aggravates the disease upon new virus exposure. Recognition of the virus epitope that induces production of the enhancing antibodies is existential necessity for safe and effective PEDV vaccine design. In this study, the enhancing epitope of the PEDV spike protein was revealed for the first time, by using phage display technology and mouse monoclonal antibody (mAbG3) that bound to PEDV S1 subunit of the spike (S) protein and enhanced PEDV entry into permissive Vero cells that lack Fc receptor. The phages displaying mAbG3-bound peptides derived from the phage library by panning with the mAbG3, matched with several regions in the S1-0 sub-domain of the PEDV S1 subunit indicating that the epitope is discontinuous (conformational). The mAbG3-bound phage sequence also matched with a linear sequence of the S1-BCD sub-domains. Immunological assays verified the phage mimotope results. Although the molecular mechanism of ADE caused by the mAbG3 via binding to the newly identified S1 enhancing epitope await investigation, the data obtained from this study are helpful and useful in designing safe and effective PEDV protein subunit/DNA vaccine devoid of the enhancing epitope.